Trends in the burden of HPV-associated cancers in Mexico: An analysis from 2011 to 2019 - Juan Carlos Orengo; Ana Luiza Bierrenbach; Carlos Eduardo Aranda Flores; Elsa Diaz Lopez; Julio Cesar Barbour Oliveira; Rodrigo Gonçalves Queijo; Cintia Irene Parellada (PLoS ONE, 2025)
Human papillomavirus (HPV) is a major public health concern, responsible for multiple types of cancer. This study aimed to provide an overview of the burden and temporal trends of HPV-associated cancers in Mexico using national hospital discharge and mortality databases from 2011–2019, including cervical, vulvar, vaginal, penile, anal, oropharyngeal, oral cavity, and laryngeal cancers. Hospitalization and mortality rates per 100,000 population were estimated; HPV-attributable fractions applied, and age-standardized temporal trends evaluated using joinpoint regression. Cervical cancer was the leading contributor, accounting for 88.5% of hospitalizations and 90.9% of HPV-attributable deaths. Hospitalization rates for cervical cancer increased between 2011–2014 (APC = 7.5%, 95% CI: 2.3, 18.0), then declined (APC = −3.0%, 95% CI: −7.8, −0.9). Other HPV-associated cancers had lower hospitalization rates, generally below 1 per 100,000, except for penile and head and neck cancers in males. Significant increases in hospitalization rates were observed in males for anal cancer from 2011–2019 (APC = 7.1%, 95% CI: 0.8, 15.1) and oropharyngeal cancer from 2017–2019 (APC = 18.0%, 95% CI: 4.0, 31.6), while in females, for vaginal cancer from 2017–2019 (APC = 30.7%, 95% CI: 10.6, 45.3) and oral cavity cancer from 2011–2019 (APC = 8.4%, 95% CI: 2.4, 29.1). Mortality for most cancers showed decreasing or stable trends over the study period, except for vulvar cancer in females (AAPC = 1.9%, 95% CI: 0.4, 4.1) and oropharyngeal cancer in both sexes (AAPC = 4.0%, 95% CI: 0.7, 8.0). Across most cancers, males were hospitalized at older ages but died younger than females, except for anal cancer. Overall, the burden of HPV-associated cancers is substantial. While cervical cancer remains prevalent and requires continued elimination efforts, the rising burden of anal and oropharyngeal cancers among males, highlights the need to strengthen public health strategies and raise awareness of HPV’s broader impact across both sexes.